2007
DOI: 10.1002/jcp.21189
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin‐rich microfibrils: Structural determinants of morphogenetic and homeostatic events

Abstract: Fibrillin-rich microfibrils are specialized extracellular matrix assemblies that endow connective tissues with mechanical stability and elastic properties, and that participate in the regulation of organ formation, growth and homeostasis. Their physiological importance is underscored by the complex spectrum of clinical manifestations associated with mutations of fibrillin-1 and fibrillin-2 in Marfan syndrome (MFS) and congenital contractural arachnodactyly, respectively. Early evidence suggested that fibrillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 45 publications
1
76
0
6
Order By: Relevance
“…Fibrillin-1 is a component of microfibrils that provide a connection between elastin fibers and vascular smooth muscle cells to provide signaling for homeostasis within the aortic wall. 13 Structural homology between the fibrillins and latent TGF-␤-binding proteins suggests an additional role for fibrillin-1 in targeting TGF-␤ to the extracellular matrix and keeping it in an inactive state. A deficiency of fibrillin-1 therefore would lead to excessive TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillin-1 is a component of microfibrils that provide a connection between elastin fibers and vascular smooth muscle cells to provide signaling for homeostasis within the aortic wall. 13 Structural homology between the fibrillins and latent TGF-␤-binding proteins suggests an additional role for fibrillin-1 in targeting TGF-␤ to the extracellular matrix and keeping it in an inactive state. A deficiency of fibrillin-1 therefore would lead to excessive TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Functional binding studies identified distinct sites on MAGP-1 for binding to tropoelastin and fibrillin-1 and -2, consistent with it being a bridging molecule that binds tropoelastin onto the microfibril during elastin assembly (24). Recent studies with fibrillin mutant mice, however, suggest that microfibrils play little role in the initial stages of elastin assembly and, instead, contribute to tissue development and function through interactions with growth factors (25,26).…”
mentioning
confidence: 93%
“…High-molecular-weight, multiprotein assemblies called microfibrils are the functional units of fibrillins, which serve as a scaffold for the biogenesis of elastic fibers, confer structural integrity to individual organ systems, regulate growth factor signaling of TGF-␤-bone morphogenic protein (BMP) superfamily members and provide limited elasticity to tissues (Kielty et al, 2002;Charbonneau et al, 2004;Ramirez and Dietz, 2007). Extracted microfibrils from cell culture or tissues display a typical bead-on-a-string ultrastructure, having a 50 -55-nm periodicity when analyzed by electron microscopy after rotary shadowing Kielty et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrillins are mainly composed of tandem arrays of calcium-binding epidermal growth factor-like domains interspersed with TGF-␤-binding protein domains (TB/8-Cys) and hybrid domains Hubmacher et al, 2006). Mutations in fibrillins give rise to the so-called fibrillinopathies, which include Marfan syndrome and autosomal dominant Weill-Marchesani syndrome, both caused by mutations in fibrillin-1, and Beal's syndrome, caused by mutations in fibrillin-2 (Robinson et al, 2006).High-molecular-weight, multiprotein assemblies called microfibrils are the functional units of fibrillins, which serve as a scaffold for the biogenesis of elastic fibers, confer structural integrity to individual organ systems, regulate growth factor signaling of TGF-␤-bone morphogenic protein (BMP) superfamily members and provide limited elasticity to tissues (Kielty et al, 2002;Charbonneau et al, 2004;Ramirez and Dietz, 2007). Extracted microfibrils from cell culture or tissues display a typical bead-on-a-string ultrastructure, having a 50 -55-nm periodicity when analyzed by electron microscopy after rotary shadowing Kielty et al, 1991).…”
mentioning
confidence: 99%